2016
DOI: 10.21082/jae.v31n1.2013.53-69
|View full text |Cite
|
Sign up to set email alerts
|

Economies of Scale of Sugarcane Cooperatives in East Java Province and Their Influencing Factors

Abstract: ABSTRAKJawa Timur merupakan provinsi sentra tebu terbesar di Indonesia dengan banyak koperasi primer yang terlibat dalam bisnis pertebuan. Penelitian ini bertujuan untuk menguji keberadaan kondisi skala ekonomi dari koperasi-koperasi yang bergerak dalam agribisnis tebu di Provinsi Jawa Timur dan faktor-faktor yang memengaruhi skala ekonomi tersebut. Metode translog cost-function dan pendekatan produsen digunakan untuk menganalisis data panel dari koperasikoperasi responden pada periode 2008-2011. Hasil penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…For instance, cooperative as one of sugarcane farmers' institutions is yet to be supervised conforming managerial functions. Similar argument was stated by (Ariningsih, 2013)who concluded that most of sugarcane farmers cooperative in East Java was at state of diseconomies of scale or operated inefficiently. In addition, institutional leadership factor is commonly so top-down in nature that aspiration and decision only emanate from a group of people.…”
Section: Discussionsupporting
confidence: 66%
“…For instance, cooperative as one of sugarcane farmers' institutions is yet to be supervised conforming managerial functions. Similar argument was stated by (Ariningsih, 2013)who concluded that most of sugarcane farmers cooperative in East Java was at state of diseconomies of scale or operated inefficiently. In addition, institutional leadership factor is commonly so top-down in nature that aspiration and decision only emanate from a group of people.…”
Section: Discussionsupporting
confidence: 66%